"De tycka emellertid av gammal vana att det smakar gott, och tro dessutom att det är bra för hälsan" - Qvarnström, Elin (2007)
Meat and fish was the most important food for the Sami people in northern Scandinavia until the beginning of the 20th century. It is not so well known that the Sami people also used a lot of wild plants as food and medicine although that kind of food was relatively common among them until the end of the 19th century. The purpose of this master thesis has been to describe which plants the Sami people used in general and also which plants were the most commonly used, and when and how these plants were harvested. I also wanted to measure the quantities of Angelica archangelica and Rumex acestosa within traditional harvest sites. Furthermore I wanted to find out if the plant use differed among Sami groups geographically. My last issue was to find out if there were any similarities between the Sami people and other circumpolar people's when it comes to plant use. For this purpose I have used old and new literature, ethnological material, field studies and interviews.